Magneto-fluorescent nanoparticles with high-intensity NIR emission, T1- and T2-weighted MR for multimodal specific tumor imaging1. Issue 15 (21st April 2015) - Wang, Guannan; Zhang, Xuanjun; Liu, Yaxu; Hu, Zhangjun; Mei, Xifan; Uvdal, Kajsa
<x xml:space="preserve">Abstract</x> Fe3O4@NIR semiconducting polymer nanoparticles were used for both T1-, T2-weighted MRI and fluorescence imaging of targeted tumors.